Hubungan antara Partisipasi Siswa dalam Kegiatan Sekolah dan Perilaku Prososial pada Siswa Sekolah Menengah Katolik - Romaria Magdalena Naibaho; Theresia Galuh; Sesilia Adhi Wahyu Utami (Jurnal Penelitian Pendidikan Agama Katolik, 2023)
This study aims to determine the relationship between student participation and prosocial behaviour in Catholic Senior High School students. The research method used is quantitative, with a correlational approach between variables. The subjects of this study were Catholic High School students in the Episcopal Vicariate of Kedu area, namely SMA Tarakanita Magelang, SMA Pangudi Luhur Van Lith, and SMK Pangudi Luhur Muntilan with a total of 295 respondents. The measurement tools used are the Student Participation Scale and the adaptation of the Prosocial Behaviour Scale. The analysis technique used is the productmoment correlation technique from Spearman's rho. The results of this study indicate that (a) there is a negative and significant relationship between participation and the public dimension with a coefficient value of -0.180 (p=0.000<0.05), (b) there is a positive and significant relationship between participation and the anonymous dimension of 0.240, emotional of 0.181, and compliant with a coefficient of 0.240 with (p=0.000<0.05). Besides that, there are two relationships between participation and dire and altruism dimensions which cannot be known because the linearity requirement is not fulfilled.